Partisan Polarization on Black Suffrage, 1785–1868. Issue 2 (20th June 2020) - Bateman, David A.
Abstract : I offer a new perspective on the history of American democratization, tracing the evolution of conflict over black suffrage from the disenfranchisements of the early Republic to efforts to secure equal voting rights in the pre-Civil War era. I draw on case studies and new data on state politics to substantially expand our descriptive understanding of the ideological connotations of African American political rights. In contrast to existing literature, this study identifies a transformation in how positions on black suffrage polarized along party lines. It also offers a new interpretation for this racial realignment, presenting evidence that legislators responded less to the electoral consequences of black voting than to efforts of party leaders and social movements to frame its denial as necessary for national unity, a pragmatic accommodation to racist public opinion, or as complicity in slavery and a violation of republicanism. Integrating earlier periods of disenfranchisement and antislavery activism recasts standard party-driven accounts of Reconstruction-era enfranchisements as the culmination of a long process of biracial social movement organizing, enriching our understanding of how both electoral and programmatic concerns contribute to suffrage reforms and of the process by which conflict over citizenship has at times become a central cleavage in American politics.